Liquid composite additive capable of replacing antioxidant 1076

Through the multi-component synergistic effect of liquid composite additives, the problems of high usage cost and application limitations of antioxidant 1076 are solved, and more comprehensive protective effect and material processing optimization are achieved. They are suitable for plastics, rubber and other industries, providing high The dual advantages of efficiency and green production.

CN119320514APending Publication Date: 2025-01-17PUYANG ZHONGYUAN PETROCHEMICAL IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411565008.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Due to the high price and concentrated resource consumption, antioxidant 1076 has increased usage costs and limited application, and a composite additive that can replace it is needed to reduce costs and expand the scope of use.

Method used

Develop a liquid composite additive consisting of pentaerythritol, di-tert-butyl p-cresol, acid binding agent, phosphorus trichloride toluene solution, petroleum ether, surfactant, catalyst, D301 resin, methanol and anhydrous ethanol, through Multicomponent synergistics provide a more comprehensive and efficient free radical scavenging capability instead of single antioxidant 1076.

Benefits of technology

This composite additive not only extends the service life of the material, reduces production costs and maintenance costs, but also optimizes the processability and thermal stability of the material, increases the scope of use of antioxidants, and provides a more comprehensive protective effect. In plastics, rubber and other industries, we have achieved the dual advantages of high efficiency and green production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320514A_ABST
    Figure CN119320514A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of antioxidants, and particularly relates to a liquid compound additive capable of replacing an antioxidant 1076, which is prepared from the following raw materials in parts by weight: 10 to 15 parts of pentaerythritol, 1 to 3 parts of butylated hydroxytoluene and 2 to 5 parts of acid-binding agent. 3-5 parts of a phosphorus trichloride toluene solution, and 50 L of nitrogen; 1-5 parts of petroleum ether; 2-4 parts of a surfactant; 1-3 parts of a catalyst; 1-3 parts of D301 resin, 1-3 parts of methanol, 1-3 parts of absolute ethyl alcohol and 1-3 parts of UV2908. According to the present invention, with the research and development of the composite auxiliary agent capable of replacing the antioxidant 1076, the composite auxiliary agent can replace the antioxidant 1076, can provide the more comprehensive protection by combining with the original antioxidant, and further provides the more comprehensive and efficient free radical scavenging ability through the multi-component synergistic effect, such that the service life of the material is prolonged, and the cost is reduced; and the liquid composite additive can also optimize the processability of the material, improve the thermal stability and fluidity and reduce the degradation risk in the processing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antioxidants, and in particular relates to a liquid composite auxiliary agent capable of replacing antioxidant 1076. Background Art

[0002] Antioxidant 1076, also known as antioxidant 1076, is a highly efficient hindered phenol antioxidant. Antioxidant 1076 is a white or slightly yellow solid powder at room temperature and pressure, with a melting point between 50 and 52°C. It is insoluble in water, but soluble in a variety of organic solvents, such as ketones, aromatic hydrocarbons, aliphatic hydrocarbons, chlorinated hydrocarbons and alcohol. Antioxidant 1076 has good thermal stability, with a volatile matter of less than 0.5%, and can still maintain good stability at high temperatures. Antioxidant 1076 is widely used in polymer materials, such as polyethylene (PE), polypropylene (PP), polystyrene (PS), polyamide, polyoxymethylene, ABS resin, polyvinyl chloride (PVC) and synthetic rubber. It can effectively prevent these materials from aging and discoloration caused by light and heat, and extend the service life of the materials. In addition, antioxidant 1076 can also be used to prevent thermal oxidation aging of greases and coatings;

[0003] As an efficient antioxidant, antioxidant 1706 is relatively expensive when used, which will increase the cost when used. As a single antioxidant, it leads to concentrated consumption of resources, resulting in great limitations when used. Therefore, a composite auxiliary agent is proposed to replace antioxidant 1076. While reducing the cost when used, it enriches the use selectivity compared with a single antioxidant, and increases the use range for a single particle antioxidant. Summary of the invention

[0004] In order to solve the problems raised in the above background technology, the present invention provides a liquid composite auxiliary agent that can replace the antioxidant 1076, which has the characteristics of replacing a single antioxidant and increasing the range.

[0005] To achieve the above object, the present invention provides the following technical solution: a liquid composite auxiliary agent that can replace antioxidant 1076, composed of the following raw materials in parts by weight:

[0006] 10-15 parts of pentaerythritol, 1-3 parts of di-tert-butyl-p-cresol, 2-5 parts of acid-binding agent;

[0007] 3-5 parts of phosphorus trichloride toluene solution, 50L of nitrogen;

[0008] 1-5 parts of petroleum ether;

[0009] 2-4 parts of surfactant;

[0010] 1-3 parts of catalyst;

[0011] 1-3 parts of D301 resin, 1-3 parts of methanol, 1-3 parts of anhydrous ethanol, and 1-3 parts of UV2908.

[0012] Preferably, it is composed of the following raw materials in parts by weight:

[0013] The phosphorus trichloride toluene solution comprises 3-5 parts of phosphorus trichloride, 1-3 parts of toluene and 3-5 parts of tetrabutylammonium bromide.

[0014] Preferably, it is composed of the following raw materials in parts by weight:

[0015] The acid-binding agent comprises 3-5 parts of triethylamine, 3-5 parts of pyridine, 3-5 parts of diisopropylamine and 2-5 parts of potassium hydroxide.

[0016] Preferably, it is composed of the following raw materials in parts by weight:

[0017] The surfactant includes 1-5 parts of tetrabutylammonium chloride, 2-5 parts of trioctylmethylammonium chloride, 1-3 parts of dodecyldimethyl tertiary amine, 1-2 parts of tetraethylammonium bromide, and 1-3 parts of hexadecyltrimethylammonium bromide.

[0018] Preferably, it is composed of the following raw materials in parts by weight:

[0019] The catalyst includes 1-3 parts of dimethylformamide. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0021] Figure 1 This is a schematic diagram of the test data of the composite auxiliary agent components in the present invention;

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention develops a composite auxiliary agent that can replace antioxidant 1076. While replacing antioxidant 1076, it can combine with the original antioxidant to provide more comprehensive protection, far exceeding the protection range of single antioxidant 1076. Through the synergistic effect of multiple components, it provides more comprehensive and efficient free radical scavenging ability, thereby extending the service life of the material and reducing costs. In addition, the liquid composite auxiliary agent can also optimize the processability of the material, improve thermal stability and fluidity, reduce the risk of degradation during processing, and increase the scope of use of the antioxidant. These advantages not only extend the service life of the material, but also reduce production costs and maintenance costs, bringing the dual advantages of high efficiency and green production to industries such as plastics and rubber. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] The present invention provides the following technical scheme: a liquid composite auxiliary agent capable of replacing antioxidant 1076, which is composed of the following raw materials in parts by weight: 10-15 parts of pentaerythritol, 1-3 parts of di-tert-butyl-p-cresol, 2-5 parts of acid binding agent, 3-5 parts of phosphorus trichloride toluene solution, 50L of nitrogen, 1-5 parts of petroleum ether, 2-4 parts of surfactant, 1-3 parts of catalyst, 1-3 parts of D301 resin, 1-3 parts of methanol, 1-3 parts of anhydrous ethanol, and 1-3 parts of UV2908.

[0027] Specifically, the phosphorus trichloride toluene solution includes 3-5 parts of phosphorus trichloride, 1-3 parts of toluene, and 3-5 parts of tetrabutylammonium bromide; the acid binding agent includes 3-5 parts of triethylamine, 3-5 parts of pyridine, 3-5 parts of diisopropylamine, and 2-5 parts of potassium hydroxide; the surfactant includes 1-5 parts of tetrabutylammonium chloride, 2-5 parts of trioctylmethylammonium chloride, 1-3 parts of dodecyldimethyl tertiary amine, 1-2 parts of tetraethylammonium bromide, and 1-3 parts of hexadecyltrimethylammonium bromide; the catalyst includes 1-3 parts of dimethylformamide;

[0028] In traditional antioxidant production, tetrahydrofuran (THF) is generally used as a catalyst for production. However, tetrahydrofuran is relatively limited in use and has poor effect as a catalyst. Dimethylformamide (DMF) has a lower vapor pressure and solubility, so it has lower volatility and higher solution stability.

[0029] In addition, dimethylformamide has better solubility and reactivity, and can be more widely used in the fields of medicine, chemical industry, electronics, etc. In the preparation of composite additives used to replace antioxidants, dimethylformamide may provide a more stable reaction environment and higher reaction efficiency.

[0030] Specifically,

[0031] Specific production method of composite additives:

[0032] Preparation of Pentaerythritol:

[0033] 1) Prepare NaOH aqueous solution in advance, the concentration of NaOH aqueous solution is required to be 20% (mass fraction), and transfer the prepared NaOH solution to the prepared three-necked flask.

[0034] Weigh a certain amount of nickel-aluminum alloy into a separatory funnel and slowly add the nickel-aluminum alloy into the three-necked flask. The whole process should be carried out under stirring conditions.

[0035] Always pay attention to the temperature changes in the bottle, which must not exceed 70C. Keep it at this reaction temperature for 2 hours.

[0036] After activation, the samples were washed with distilled water until the pH value was 7.

[0037] During the entire operation, the activated nickel must not be exposed to the air.

[0038] 2) Hydrogenation in the reactor. The reactor is equipped with a stirring device with good corrosion resistance. The reaction temperature and speed of the reactor are controlled by the temperature sensing element and the speed measuring device (Hall sensor). The speed of the high-pressure reactor is controlled by the voltage of the DC motor.

[0039] Air tightness test: add some water into the autoclave, tighten the autoclave, fill the autoclave with N2 at a certain pressure, and start the stirring device.

[0040] Observe the changes in the indication of the pressure gauge on the reactor. If the pressure gauge pointer does not move, it proves that the air tightness is qualified and the reactor can be used.

[0041] If the pressure gauge pointer moves, you need to find the leak in the autoclave and repair it before using it.

[0042] During the hydrogenation process of the reactor, about 0.3 liters of ethanol solution of trimethylolacetaldehyde was added to a 0.5-liter autoclave, and a certain amount of activated Raney nickel was added to the autoclave as a catalyst. The autoclave was tightened and other parts of the autoclave were assembled.

[0043] The gas in the autoclave was replaced with H2 for 6 times to ensure that there was no oxygen in the autoclave, and then filled with hydrogen to the pressure required for the reaction.

[0044] Turn on the stirring speed to 250r / min, and slowly set the temperature to avoid the occurrence of temperature runaway, raise the temperature to the required reaction temperature, and start recording the reaction time.

[0045] At the same time, pay attention to the pressure changes in the reactor. After the pressure drops, add H2 in time to the pressure required for the reaction to ensure that the reaction is carried out under the pressure required for the experiment and reacts under this pressure for a period of time.

[0046] 3) After the reaction is completed, stop stirring and heating, cool to 25°C with water, release the pressure in the reactor, and open the reactor to take samples.

[0047] The liquid sample was vacuum filtered in time to separate the catalyst, the liquid was collected for rotary evaporation, a small amount of liquid and solid were collected in a round-bottom flask, and the mixed liquid was placed in a low temperature environment, at which time white pentaerythritol crystals were precipitated.

[0048] The solution was filtered again, washed several times with a small amount of ethanol solution, placed in a forced air drying oven for 2 hours to evaporate the ethanol attached to the product, and cooled in a dryer to obtain the target product.

[0049] The pentaerythritol produced by the above method has a better effect when used as the main material to produce a composite auxiliary agent, and the conversion rate of the produced content is higher.

[0050] 1) Weigh pentaerythritol, BHT, triethylamine and toluene in proportion, and put them into a 5L four-necked reaction bottle respectively, stir and mix the mixed solution, and cool the solution to 0-10°C for standby use;

[0051] 2) Weigh phosphorus trichloride and toluene in proportion and mix them evenly. After the solution is cooled to 10° C., add the mixed solution of phosphorus trichloride and toluene dropwise into the reaction bottle for 1 hour to allow the two mixed solutions to fully mix and react;

[0052] 3) During the dropwise addition of the mixed solution of phosphorus trichloride and toluene, hydrogen chloride (HCl) gas will be emitted for about 1.5 hours. The temperature of the mixed solution is slowly increased according to the HCl gas flow rate until the reaction temperature reaches 75°C. This process lasts for about 9 hours. For the discharged HCl gas, the staff can discharge the gas into the sodium hydroxide solution to process the HCl gas;

[0053] 4) When the reaction temperature reaches 75°C and no HCl is generated, the reaction of the mixed solution ends. After the reaction of the mixed solution is completed, the mixed solution is purged with nitrogen for 1 hour to remove the remaining phosphorus trichloride in the mixed solution by contacting the mixed solution with nitrogen. The nitrogen flow rate is 20 L / h;

[0054] 5) adding triethylamine and TBAB to the mixed solution in proportion, wherein the triethylamine is used to adjust the pH value of the reaction system, adjusting the reaction system from acidic to alkaline, and during the adjustment process, the reaction temperature of the mixed solution is increased to 110° C., and the reaction is carried out to the end point;

[0055] 6) filtering triethylamine hydrochloride under 100° C. to obtain triethylamine hydrochloride, and washing the salt with 110° C. toluene three times, cooling the obtained filtrate for crystallization, and filtering to obtain a crude composite auxiliary agent;

[0056] 7) Since a small amount of triethylamine hydrochloride is mixed in the crude product, the acid value of the crude product is greater than 1 and the initial melting point is lower than 234° C., which cannot meet the physical and chemical index requirements of the product. Methanol is used as the solvent for pulping.

[0057] The operation steps of the beating process are:

[0058] Add an appropriate amount of methanol to the crude product of the composite additive in a ratio of 2:1, and slurry the mixed solution at 20°C for 1 hour;

[0059] The product is filtered and washed three times with an equal proportion of methanol, and the filtered material is mixed with a certain amount of hexamethylenetetramine;

[0060] The mixed solution was dried at 30°C and vacuum degree 0.085 MPa at 80°C for 15 minutes to obtain a finished composite additive.

[0061] Specifically,

[0062] Compound additive composition inspection:

[0063] Reagents required for the experiment, finished composite additives, methanol and water;

[0064] Equipment required for the experiment, spectrometer and chromatograph;

[0065] Spectral analysis, the principle of IR analysis is that when the sample is irradiated by an infrared light source, the sample molecules can absorb infrared light with the same frequency as the fundamental frequency of the chemical bond vibration. The sample molecules vibrate and transition to energy levels due to the absorption of energy, and infrared light is also absorbed by the molecules due to certain frequencies, forming an infrared absorption spectrum.

[0066] By the attached Figure 1 It can be seen that

[0067] The propionic acid (a) carried in the finished composite additive showed a characteristic absorption peak of carboxyl group vc=0 at 1710 cm1. Compared with the three antioxidants ((b), (c) and (d)), the characteristic absorption peak of amide vc=0 (amide I band) was at 1652 cm1, proving that hexamethylenediamine, p-phenylenediamine and 1.0G dendrimer reacted with β-(3-methyl-5-tert-butyl-4-hydroxyphenyl) propionic acid.

[0068] The characteristic peak of the carbonyl group shifted to a lower wavenumber by 58 cm1. This is because the N atom and C=O undergo a pn conjugation effect and overlap well. The influence of the conjugation effect exceeds the inductive effect of the N atom, resulting in the averaging of the electron cloud density of the C=O double bond, a decrease in the properties of the double bond, and the shift of the absorption peak to a lower wavenumber.

[0069] In addition, the absorption peaks of the three semi-hindered phenol antioxidants at 3304cm-1 are the NH stretching vibration absorption peaks of the amide bond.

[0070] In order to more clearly illustrate the absorption peaks of the characteristic functional groups of the three antioxidant molecules, their infrared characteristic absorption peaks were assigned, and the absorption peak of free OH was not seen in the results. Other characteristic functional groups all showed corresponding characteristic absorption peaks. The appearance of these characteristic peaks preliminarily indicated that the structure of the synthesized finished composite additive was basically consistent with that of the other three antioxidants.

[0071] The composite auxiliary agent is then subjected to chromatographic analysis. When using high performance liquid chromatography, the liquid sample is injected into the chromatographic column, and pressure is applied to make the sample move in the stationary phase. Due to the differences in the interactions between different substances and the stationary phase, they leave the chromatographic column in sequence, and different peak signals are obtained through the detector. Finally, these signals are analyzed and compared to determine the substances contained in the sample.

[0072] High performance liquid chromatography is an important analytical detection method, which is widely used in chemical and biochemical analysis. The working principle of high performance liquid chromatography is similar to that of classical liquid chromatography. Its characteristics are that it uses a high-pressure infusion pump, a high-sensitivity detector and a high-efficiency particulate stationary phase. It is suitable for analyzing organic compounds with high boiling points, low volatility, large molecular weight and different polarity.

[0073] Specifically,

[0074] Stability test of composite additives:

[0075] The hydrolysis stability of the composite additive was tested in a constant temperature oven at 60°C and 75% relative humidity. The composite additive was sampled regularly during the hydrolysis process and dissolved in acetonitrile to prepare a solution of a certain concentration (5 mg / L). The solution was analyzed and tested using a Shimadzu liquid chromatography (C18 column, UV Detector 240or245nm, chromatographically pure acetonitrile as the mobile phase, and the injection volume was 10uL). The degree of hydrolysis of the composite additive was represented by the consumption of the main content composite additive.

[0076] Degree of hydrolysis = (Ao-At) / Ao×100%

[0077] Wherein, A0 represents the main peak area of ​​the antioxidant before hydrolysis, and At represents the peak area of ​​the main content antioxidant at a certain time.

[0078] Specifically,

[0079] Composite additive effect experiment:

[0080] Antioxidant comparison experiment of antioxidant 1076 and composite additives

[0081] Reagents required for the experiment: antioxidant 1076 (referred to as antioxidant A), finished composite additive (referred to as composite additive B), polyethylene (PE) powder (base material) and heat stabilizer (calcium stearate);

[0082] Equipment required for the experiment, accelerated aging test equipment (UV aging test chamber) and differential scanning calorimeter (DSC);

[0083] Experimental Procedure

[0084] 1. Mix polyethylene powder and antioxidant A in a certain proportion

[0085] Then, the polyethylene powder and the composite additive B are evenly mixed in a certain proportion.

[0086] 2. Prepare PE samples containing only antioxidant A (sample 1) and PE samples containing compound additive B (sample 2), and set up a PE blank control sample without any additives (sample 3).

[0087] 3. Place all samples in the UV aging test chamber at the same time, and conduct accelerated aging experiments under set high temperature conditions to keep the conditions of all samples consistent during the experiment.

[0088] 4. When conducting accelerated aging experiments on samples, staff used a differential scanning calorimeter (DSC) to measure the oxidation induction time of the samples.

[0089] 5. Record the experimental data, including the aging condition and OIT value of the samples.

[0090] The experimental data are shown in the following table:

[0091]

[0092]

[0093] Table 1

[0094] According to Table 1, both antioxidant A and composite additive B can effectively improve the antioxidant properties of polyethylene and prolong its oxidation induction time.

[0095] Composite additive B exhibits superior antioxidant performance, and its OIT value is higher than that of antioxidant A.

[0096] The antioxidant performance of the blank sample was the worst, indicating that the additive had a significant effect on improving the antioxidant performance.

[0097] As a new type of additive, composite additive B shows greater potential in antioxidant performance and may have broader industrial application prospects.

[0098] However, the functional testing of the composite additive on a single substrate and the comparison with antioxidant 1076 are limited and cannot fully explain the application effect of the antioxidant. Other substrates need to be selected for testing and comparison.

[0099] Antioxidant experiment of composite additives on different substrates

[0100] Reagents required for the experiment: composite additive B (antioxidant), polypropylene (PP) particles, polystyrene (PS) particles, thermoplastic elastomer (TPE) particles;

[0101] Equipment required for the experiment, accelerated aging test equipment (UV aging test chamber) and differential scanning calorimeter (DSC);

[0102] 1. Mix the composite additive B with different base materials at 1% (by weight) respectively.

[0103] 2. Prepare PP samples (sample PP-B), PS samples (sample PS-B) and TPE samples (sample TPE-B) containing composite additive B respectively, and set up corresponding substrate blank control samples (samples PP-0, PS-0, TPE-0) without any additives.

[0104] 3. Place all samples in a UV aging test chamber and conduct accelerated aging experiments under the same high temperature conditions.

[0105] 4. The oxidation induction time of the samples was measured using a differential scanning calorimeter (DSC).

[0106] 5. Record the experimental data, including the aging condition and OIT value of the samples.

[0107] The experimental data are shown in the following table:

[0108]

[0109] Table 2

[0110] According to the data in Table 2, it can be seen that composite additive B can improve the antioxidant properties of the material in different substrates and prolong its oxidation induction time.

[0111] Composite additive B has the best antioxidant performance in TPE, and its OIT value is significantly higher than that of the other two substrates.

[0112] In PP and PS substrates, compound additive B also exhibits good antioxidant properties, but the effect is slightly inferior to that of TPE.

[0113] The aging degree of blank control samples of each substrate is more obvious, and the OIT values ​​are lower than those of the corresponding samples with composite additive B added.

[0114] Therefore, it can be concluded that the composite additive can replace the function of antioxidant 1076 when applied to a specific substrate for antioxidant treatment.

[0115] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A liquid composite auxiliary agent that can replace antioxidant 1076, characterized in that: It is composed of the following raw materials in parts by weight: 10-15 parts of pentaerythritol, 1-3 parts of di-tert-butyl-p-cresol, 2-5 parts of acid-binding agent; 3-5 parts of phosphorus trichloride toluene solution, 50L of nitrogen; 1-5 parts of petroleum ether; 2-4 parts of surfactant; 1-3 parts of catalyst; 1-3 parts of D301 resin, 1-3 parts of methanol, 1-3 parts of anhydrous ethanol, and 1-3 parts of UV2908.

2. A liquid composite auxiliary agent that can replace antioxidant 1076 according to claim 1, characterized in that: It is composed of the following raw materials in parts by weight: The phosphorus trichloride toluene solution comprises 3-5 parts of phosphorus trichloride, 1-3 parts of toluene and 3-5 parts of tetrabutylammonium bromide.

3. A liquid composite auxiliary agent that can replace antioxidant 1076 according to claim 1, characterized in that: It is composed of the following raw materials in parts by weight: The acid-binding agent comprises 3-5 parts of triethylamine, 3-5 parts of pyridine, 3-5 parts of diisopropylamine and 2-5 parts of potassium hydroxide.

4. A liquid composite auxiliary agent that can replace antioxidant 1076 according to claim 1, characterized in that: It is composed of the following raw materials in parts by weight: The surfactant includes 1-5 parts of tetrabutylammonium chloride, 2-5 parts of trioctylmethylammonium chloride, 1-3 parts of dodecyldimethyl tertiary amine, 1-2 parts of tetraethylammonium bromide, and 1-3 parts of hexadecyltrimethylammonium bromide.

5. The liquid composite auxiliary agent capable of replacing the antioxidant 1076 according to claim 1, characterized in that: It is composed of the following raw materials in parts by weight: The catalyst includes 1-3 parts of dimethylformamide.